PENERAPAN GAME EDUKATIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SETINGKAT MADRASAH IBTIDAIYAH - Supriyono, Heru (WARTA, 2018)
Partners of this community services program are MIM Potronayan 1 and MIM PK Kenteng. One of problems faced by those schools is students get bored easily when attending the class, in this case is learning Aksara Jawa. Based on observations conducted previously, it could be noted that the root of the problem is both schools were only used printed materials for teaching in the class which is not interactive. In this community services, the team offer a multimedia-based learning media with educational game. The learning media mainly was developed using Construct 2 software. The objective of the community services is to implement the interactive learning media with educational game of Aksara Jawa for elementary school teachers and students. The results of the community services are involving application program of interactive learning media for computer and mobile computing devices, and teachers have been introduced with interactive learning media. The evaluation result showed that 91% teachers and students feel the application program increase student motivation for learning Aksara Jawa very significantly.